Heterogeneous Interfaces of Magnetic CIP and Binary Dielectric Carbon-Based Material Toward High-Efficiency Microwave Attenuation - Song, Yongzhi; Bi, Song; Hou, Genliang; Li, Hao; Liu, Zhaohui (Frontiers in Materials, 2022)
-based matCarbon-based materials, as lightweight absorbers, have been widely applied in varied fields to counteract the adverse effects of electromagnetic waves. Nevertheless, there remain challenges in coping with the impairment of microwave absorption performance caused by the excessively high permittivity of carbon materials. Herein, carbonyl iron powder (CIP) was added to graphene oxide/carbon black (RGO-CB) composites to adjust the permittivity improving impedance matching and electromagnetic absorption properties. In this work, the RGO provides a three-dimensional structure net, which introduces circularly and variously electromagnetic loss interfaces within the RGO-CB/CIP composites. Owing to the unique architecture and synergy of the three components, the as-prepared absorber exhibits good impedance matching and gratifying microwave absorption properties. It was found that the 1:1 mixture of RGO-CB and CIP in the composite had superb impedance matching at the thicknesses of 2.6 and 2.7 mm to achieve full X-band microwave absorption. Such excellent performance benefit from the multiple polarization provided by the heterogeneous interfaces and the superior impedance match attributed to the tunable permeability and permittivity of this work.erial toward high-efficiency m